Flexible Etherified and Esterified Triphenylethylene Derivatives and Their Evaluation on ER‐positive and Triple‐Negative Breast Cancer Cell Lines. (17th February 2022) - Hassan, Aya S.; Wober, Jannette; Vollmer, Günter; Abadi, Ashraf H.; Ahmed, Nermin S.
Abstract: Tamoxifen (TAM) is a selective estrogen receptor modulator (SERM) with potential clinical benefits for all stages of breast cancer. TAM is primarily metabolized to more potent metabolites via polymorphic CYP2D6. This affects the clinical outcome of TAM treatment. Herein we report novel TAM analogues that can avoid metabolism via CYP2D6. The novel analogues bear a flexible skeleton. Compounds have either an ester group on ring C or homodiaminoalkoxy groups on rings B and C . Compound 6 ( E/Z ‐4‐[1‐[4‐(2‐diethylaminoethoxy)phenyl]‐3‐(4‐methoxyphenyl)‐2‐methyl[propenyl]phenol) was found to be ten‐fold more potent than TAM on MCF‐7 cells (GI50 =0.15 μM). It showed fivefold greater inhibitory activity on MDA‐MB‐231 cells than TAM (GI50 =1.71 μM). Compound 13 (4‐{3, 3‐bis‐[4‐(3‐dimethylaminopropoxy)phenyl]‐2‐methylallyl}methoxybenzene) was the most potent among the homodiaminoalkoxy derivatives (GI50 =0.44) on both MCF‐7 and MDA‐MB‐231 cell lines, respectively. Furthermore, the COMPARE algorithm suggested that it has different molecular targets from those of some other reported anticancer drugs. Abstract : We introduced structural modifications on the triphenylethylene backbone of selective estrogen receptor modulators. The changes influenced ER activity and the ability of compounds to inhibit the growth of ER‐positive and ‐negative breast cancer cell lines. Some compounds were found to be more potent than tamoxifen. Some compounds were prepared as prodrugs to overcome the polymorphic nature of CYP2D6, a major enzyme in tamoxifen metabolism.